ZORORO SHOPPING WEBSITE - P.Harpal Singh, Keshweenpal Singh (IRC, 2020)
As today there are many ecommerce website exist that have earned million even billion depending on how popular and trustable the website is. Even in Malaysia there are a few ecommerce website that have proved to be successful such as Lazada and Mudah. A good ecommerce have the ability to generate big sales in which may involves international transaction. Having international transaction can improves a developing country’s economy when product sales can improves economy currency while bringing country name to another level. This can be seen when Shopee is from Singapore hence through transaction the economy rises too. An ecommerce website is a useful platform where people rather purchase items online and have the item delivered to their doorstep. A good item are sold fast while other items takes time to sell depending on customer demands. What if there is a way to predict customer behaviour in the future on who likes which item so that right promotion can be done to the targeted customer to increase sales even higher than usual. There are 2 side of an ecommerce website, first is the customer side where new user needed to login while old customer just sign in and from there customers can view product which they prefer and add those product to cart. Then payment is done and customers are able to get the items delivered to their doorstep, It’s even better when customer added similar products that are recommended by system based on overall customer preference. Another side is the admin site where admin can add/delete products, add/delete categories, add/ delete brands of product and view order history.